Emerging pharmacologic interventions for pre-eclampsia treatment. (3rd August 2022) - Zhang, Xiao; Chen, Yue; Sun, Dongli; Zhu, Xiaojun; Ying, Xia; Yao, Yao; Fei, Weidong; Zheng, Caihong
ABSTRACT: Introduction: Pre-eclampsia is a serious pregnancy complication and a major global concern for the mortality of both mother and fetus. Existing symptomatic treatments do not delay disease progression; thus, timely delivery of the baby is the most effective measure. However, the risk of various maternal and fetal injuries remains. Areas covered: In this review, we summarize potential strategies for pharmacologic interventions in pre-eclamptic therapy. Specifically, we discuss the pathophysiological process of various effective candidate therapeutics that act on potential pathways and molecular targets to inhibit key stages of the disease. We refer to this pathogenesis-focused drug discovery model as a pathogenesis–target–drug (P–T–D) strategy. Finally, we discuss the introduction of nanotechnologies to improve the safety and efficacy of therapeutics via their specific placental targeting ability and placental retention effects. Expert opinion: Despite the active development of novel pharmacological treatments based on our current knowledge of pre-eclamptic pathogenesis, investigations are still in the early phase. Thus, further exploration of the pathological mechanisms, integrated with the P–T–D strategy and novel nanosystems, could encourage more effective and safer strategies. Such advances could lead to a shift from expectant management to mechanistic-based therapy for pre-eclampsia. uf0001